2013
DOI: 10.1590/s0036-46652013000400002
|View full text |Cite
|
Sign up to set email alerts
|

Soil Contamination in Public Squares in Belo Horizonte, Minas Gerais, by Canine Parasites in Different Developmental Stages

Abstract: SUMMARYTo evaluate soil contamination by parasites in different developmental stages in public squares used as recreation and leisure areas for children in Belo Horizonte (MG, Brazil), 210 soil samples and 141 canine fecal samples were collected from 42 squares in the city. These samples were analyzed by the Caldwell and Caldwell technique and the Hoffman, Pons, and Janer technique. Of the samples analyzed, 89 (42.4%) soil samples and 104 (73.5%) fecal samples were contaminated with Ancylostoma sp., Toxocara s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
0
10
0
6
Order By: Relevance
“…Other studies analyzed samples from parks, schools/day care centers, beaches, riversides and plantation areas. 25 Peridomiciliar areas and schools Marques et al, 2012 26 Public parks and schools Moura et al, 2012 27 Public parks Santarém et al, 2012 28 Public parks Saito and Rodrigues, 2012 29 Peridomiciliar areas Brilhante et al, 2013 2 Peridomiciliar areas Moura et al, 2013 30 Public squares Ribeiro et al, 2013 31 Public parks Onuma et al, 2014 32 Peridomiciliar areas Silva et al, 2014 33 Planting areas Sousa et al, 2014 11 Beaches Sprenger et al, 2014 34 Public parks and squares Prestes et al, 2015 35 Public squares Amorim and Souza, 2016 9 Beaches Maciel et al, 2016 36 Public squares Silva et al, 2016 37 Peridomiciliar areas Bortolatto et al, 2017 38 Parks and squares Fontes et al, 2017 39 Parks and squares Handam et al, 2017 40 Schools Ignácio et al, 2017 41 Peridomiciliar areas Marino et al, 2017 42 Peridomiciliar areas Neto et al, 2017 43 Parks Souza and Almeida, 2017 44 Beaches Andrade et al, 2018 45 Peridomiciliar areas Capella et al, 2018 46 Vulnerable communities Gonçalves and Paludo, 2018 47 Public squares Mota et al, 2018 48 Parks, squares, among others Vidal et al, 2019 49 Public locations (parks, flower beds and sidewalks) Silva et al, 2019 50 Roads and public squares Eisen et al, 2019 51 Park…”
Section: Resultsmentioning
confidence: 99%
“…Other studies analyzed samples from parks, schools/day care centers, beaches, riversides and plantation areas. 25 Peridomiciliar areas and schools Marques et al, 2012 26 Public parks and schools Moura et al, 2012 27 Public parks Santarém et al, 2012 28 Public parks Saito and Rodrigues, 2012 29 Peridomiciliar areas Brilhante et al, 2013 2 Peridomiciliar areas Moura et al, 2013 30 Public squares Ribeiro et al, 2013 31 Public parks Onuma et al, 2014 32 Peridomiciliar areas Silva et al, 2014 33 Planting areas Sousa et al, 2014 11 Beaches Sprenger et al, 2014 34 Public parks and squares Prestes et al, 2015 35 Public squares Amorim and Souza, 2016 9 Beaches Maciel et al, 2016 36 Public squares Silva et al, 2016 37 Peridomiciliar areas Bortolatto et al, 2017 38 Parks and squares Fontes et al, 2017 39 Parks and squares Handam et al, 2017 40 Schools Ignácio et al, 2017 41 Peridomiciliar areas Marino et al, 2017 42 Peridomiciliar areas Neto et al, 2017 43 Parks Souza and Almeida, 2017 44 Beaches Andrade et al, 2018 45 Peridomiciliar areas Capella et al, 2018 46 Vulnerable communities Gonçalves and Paludo, 2018 47 Public squares Mota et al, 2018 48 Parks, squares, among others Vidal et al, 2019 49 Public locations (parks, flower beds and sidewalks) Silva et al, 2019 50 Roads and public squares Eisen et al, 2019 51 Park…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the results of one study from Brazil showed that the soil samples were contaminated with this parasite with a prevalence rate of 2.3% (18) and therefore further studies on this region are necessary. However, the difference among the prevalence rates of this parasite in different countries or different regions of a country is likely due to various geographical climates, host distribution and many other factors (19).…”
Section: Resultsmentioning
confidence: 99%
“…Apesar de todos estes fatores expressivos, as síndromes e doenças causadas pelo Toxocara sp. no homem são subdiagnosticadas o que favorece a negligenciação de sua prevalência e incidência atuais 15,49,52 .…”
Section: Toxocara Sp Como Agente De Doença No Homemunclassified
“…O diagnóstico sorológico é realizado pelo teste imunoenzimático (ELISA) no qual são utilizados produtos antigênicos obtidos de cultura de larvas de T. canis -antígenos excretores-secretores (TES). Este método é amplamente usado nos inquéritos sorológicos em diferentes estudos no Brasil 25,35,48,51,52,58,60,66,74,77,85 , considerado de boa acurácia, possui limitação de ter reação cruzada com outros parasitos em países onde a infecção é prevalente. Como alternativa para minimizar esta desvantagem, normalmente, o soro é adsorvido com extratos de Ascaris suum antes dos testes para evitar a reação cruzada principalmente com Ascaris lumbricoides 10,47,52,74,77,85 .…”
Section: Diagnósticounclassified